Women's experiences of pharmacological of Non- Pharmacological Pain Relief Therapy: Qualitative Systematic Review (International Journal of Food and Nutritional Sciences, 2022)
Most of the mother adopt non pharmacological pain reducing methods during their child birth. The reviews reveal that effective pain relief methods were associated with mother’s satisfactionlevel. Mother’s views and experience on non pharmacological pain reducing methods like music therapy, relaxation technique and massage were studied. Nearly 10 electronic data base were searched. Thematic and meta-ethnographic techniques for data analysis purposes and GRADE-CERQual approach to assess confidence in review findings were used. Among 48 research paper twenty-four studies provided findings for the synthesis: music (n =5), relaxation (n=3) and massage (n =5) all conducted and mothers in active stage of labour. Re-analysis of the review findings generated five key themes. ‘Impact on pain’ describes varying levels of effectiveness of non pharmacological methods used.Mothers possess different types of experiences in pain reduction methods .The non Pharmacological methods reduce pain with no negative side-effects. It facilitates bonding with professionals. Mothers need more information and benefits of all available pain reducing methods.